The Emergence of Unfair Competition among Notaries as a Result of Violations of the Notary Code of Ethics: Timbulnya Persaingan Tidak Sehat Antar Notaris Sebagai Dampak Dari Pelanggaran Kode Etik Notaris - Prihayuningtyas, Anggita Kusuma; Ana Silviana (Lex Renaissance, 2023)
In carrying out their positions, notaries are obligated to work professionally and to refer to the Notary Code of Ethics which is regulated in Law Number 2 of 2014 on the Position of Notaries (UUJN). The existence of a notary has the aim of providing legal services to the community, especially in terms of making deeds. As legal needs increase, the need for notary services increases. Unhealthy competition that occurs between fellow notaries can of course occur in various forms and ways. The aim of this research is to identify how the notary code of ethics is enforced and the factors that cause violations of the notary's Code of Ethics which give rise to unhealthy competition between fellow notaries. This research is normative in nature where a statutory regulation approach is taken, collecting data using literature and document studies, the data analysis method used is qualitative. The results of the research include, first, efforts that can be made to enforce the code of ethics, the Central Honorary Council together with the Central Management of the Indonesian Notary Association by making regulations embodied in PDKP INI. Second, the increasing public need for legal activities that require authentic deeds, and the increasing number of people who work as Notaries, are reasons for Notaries to take actions that result in unhealthy competition among some Notaries.Keywords: competition, notary, code of ethics AbstrakNotaris dalam menjalankan jabatannya harus bekerja profesional dan mengacu kepada Kode Etik Notaris yang telah diatur dalam Undang-Undang Nomor 2 Tahun 2014 tentang Jabatan Notaris (UUJN). Keberadaan notaris memiliki tujuan utuk memberikan pelayanan hukum kepada masyarakat khususnya dalam hal pembuatan akta. Semakin bertambahnya kebutuhan hukum, semakin meningkat pula kebutuhan akan jasa notaris. Persaingan tidak sehat yang terjadi antar sesama rekan notaris tentu dapat terjadi dalam berbagai bentuk dan cara. Tujuan penelitian ini adalah untuk mengetahui bagaimana penegakan dalam pelaksanaan kode etik notaris serta faktor penyebab pelanggaran kode etik notaris yang menimbulkan persaingan tidak sehat antar sesama notaris. Penelitian ini bersifat normatif dengan pendekatan peraturan perundang-undangan. Pengumpul data dengan studi pustaka dan dokumen, metode analisis data yang digunakan adalah secara kualitatif. Hasil penelitian menyimpulkan: Pertama, upaya yang dapat dilakukan dalam penegakan kode etik Dewan Kehormatan Pusat bersama Pengurus Pusat Ikatan Notaris Indonesia dengan membuat peraturan diwujudkan dalam PDKP INI; dan Kedua, bertambahnya kebutuhan masyarakat akan kegiatan hukum yang membutuhkan adanya akta otentik, dan bertambah banyaknya orang yang berprofesi Notaris, menjadi alasan Notaris melakukan tindakan yang mengakibatkan persaingan tidak sehat di kalangan sebagian Notaris.Kata kunci: persaingan, notaris, kode etik